Career counseling : process, issues, and techniques - Gysbers, Norman C.; Heppner, Mary J.; Johnston, Joseph A. (Boston : Allyn and Bacon, 2003)
Outlining an approach to career counseling and a holistic model of human development, this book focuses on contextual issues like race, ethnicity, gender, sexual orientation, disability, and social class. While basing its prescriptions on theoretical concerns, the book outlines practical techniques.
Includes bibliographical references and index.
Keywords: Vocational guidance -- Study and teaching